Occurrence of Retinal Ganglion Cell Loss via Autophagy and Apoptotic Pathways in an Autoimmune Glaucoma Model. (1st September 2020) - Reinehr, Sabrina; Buschhorn, Verena; Mueller-Buehl, Ana M.; Goldmann, Tobias; Grus, Franz H.; Wolfrum, Uwe; Dick, H. Burkhard; Joachim, Stephanie C.
ABSTRACT: Purpose: In glaucoma, an apoptotic death of retinal ganglion cells (RGCs) has been shown. However, little is known about other cell death mechanisms, like autophagy or necrosis. Therefore, we investigated these mechanisms in addition to antibody deposits in an experimental autoimmune glaucoma model. Methods: Rats were immunized with a retinal ganglion cell-layer homogenate (RGA), while controls received sodium chloride. Untreated rats served as natїve group. After seven weeks, retinal cross-sections were stained with antibodies against RGCs (Brn-3a), apoptosis (cleaved caspase 2, cleaved caspase 3 as well as caspase 3, 8, and 9), autophagy (LC3BII and LAMP1), and necrosis (RIPK3) followed by cell counts. Autophagy was additionally visualized via transmission electron microscopy on retinal sections. Antibody deposits were also analyzed. Results: We noted a RGC loss after RGA immunization compared to both control groups. Also, significantly more cleaved caspase 2 + RGCs were observed in RGA animals. More caspase 3 and 8 signals were noted in RGA retinas compared to both controls, while no changes were seen in regard to caspase 9. Furthermore, significantly more cleaved caspase 3 + cells were detected in RGA animals. We noted an increase of LC3BII + and LAMP1 + autophagic cells in the RGA group, while no alterations were seen regarding necrotic RIPK3 + cells. Autophagic vesicles were observed via transmission electron microscopy. IgG staining revealed significant differences between the RGA group and controls concerning IgG deposits in the ganglion cell layer. Conclusions: Due to the novel results from this study, we conclude that IgG antibodies are involved in RGC loss in this model leading to apoptotic and autophagic cell loss. These results could help to develop new therapy strategies for glaucoma patients.